A comparative study of Co-situation of Postcolonialism in the Novels "Migration towards North" by Tayib Salih and "Kordadry" by Khasraw Jaff - Halmat Baiz Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The co-situation of Post colonialism in the Comparison of ‘Kordara’ and ‘Migration to the North’ The theory of post colonialism as a result of postmodern and after post-constructivist approach has theoretically opened up a new gate in literary studies. One of the most important topics and developments in the field of literary studies is the relationship between comparative literature and post colonialism. Post colonialism as a new theory has its own importance in terms of content from many different dimensions and concepts, especially Kurdish literature as a colonial and post-colonial situation contains many different characteristics. The title of this paper “The co-situation of Post colonialism in the Comparison of Kordara and Migration to the North” is aimed at the theoretical concepts of post colonialism on Kurdish literary texts. The field of comparative literature provides an appropriate example of the understanding that postcolonial literature is similar in many ways